Knowledge Development About The History And Basic Principles Of Health Insurance Business In Indonesia - Aprianti, Desi; ‘Aini, Qurotul; Puspitaloka Mahadewi, Erlina (Publisher Cv. Inara, 2023)
The health insurance in Indonesia is something new for most Indonesians because the term health insurance itself, until now after the pandemic, has not become a word that is commonly understood. The understanding of what is called health insurance is still very varied so it is not surprising, for example, in the past, many people said that the Community Health Maintenance Guarantee (JPKM) in Indonesia was not health insurance but only the name was used without using the word insurance. The Indonesian population is generally a risk taker in terms of health and death. The economic condition of the Indonesian population from independence until now has been able to have a per capita income per year, which has not allowed the Indonesian population to set aside funds to buy health insurance or life insurance. Meanwhile, from the supply side, not many insurance companies offer health insurance products. The Indonesian government has been relatively slow in introducing the concept of insurance to the public through ease of licensing and legal certainty in the insurance business ordeveloping social health insurance for the wider community. This study uses a qualitative method that aims to analyze the relationship between the development of knowledge about the basic history of health insurance related to the basic principles of health insurance in Indonesia which is expected to increase knowledge about the history of health insurance and the basic principles of health insurance. The goal of this research is to find out things that can provide compensation for losses originating from ignorance of health insurance knowledge.